2010
DOI: 10.1007/s12012-010-9094-7
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Induces Oxidative–Nitrative Stress in Heart of Rats: Prevention by Folic Acid

Abstract: Hyperhomocysteinemia is a risk factor for cardiovascular disease, stroke, and thrombosis; however, the mechanisms by which homocysteine triggers these dysfunctions are not fully understood. In the present study, we investigated the effect of chronic hyperhomocysteinemia on some parameters of oxidative stress, namely thiobarbituric acid reactive substances, an index of lipid peroxidation, 2',7'-dichlorofluorescein (H(2)DCF) oxidation, activities of antioxidant enzymes named superoxide dismutase and catalase, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 55 publications
3
35
2
Order By: Relevance
“…It also reduced methionine-induced oxidative stress in the aorta and heart [30,31]. The ability of folate to reduce oxidative stress was recently reported elsewhere [18,36].…”
Section: Discussionmentioning
confidence: 80%
“…It also reduced methionine-induced oxidative stress in the aorta and heart [30,31]. The ability of folate to reduce oxidative stress was recently reported elsewhere [18,36].…”
Section: Discussionmentioning
confidence: 80%
“…Handy et al [34] previously demonstrated that homocysteine decreases glutathione peroxidase activity by altering the specific translational mechanism essential for the synthesis of this selenocysteine-containing protein. Superoxide dismutase protein levels in the heart were reduced in a dog model [35] and in a rat model of chronic hyperhomocysteinemia [36]. Production of reactive oxygen species is increased by hyperhomocysteinemia.…”
Section: Discussionmentioning
confidence: 96%
“…Kolling et al [17] showed that Hcy increased lipid peroxidation and TBARS level in rats' heart. Lipid peroxidation was also observed in the liver of rats, and was associated with Hcyinduced cell injury, including apoptosis and infl ammation in liver disease [12,13].…”
Section: Discussionmentioning
confidence: 98%